Pengaruh Perubahan Organisasi, Keterlibatan Kerja dan Komunikasi Interpersonal terhadap Kinerja Karyawan pada Bank Sultra Cabang Baubau - Muliana Ayu Bashari; Nurwati Nurwati; La Hatani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study originated from the urgent need to enhance staff work efficiency in facing organizational competitive pressures, particularly in regional banking. The research aims to examine the influence of structural transformation, work participation intensity, and interpersonal interaction on productivity, both collectively and individually. The method employed is quantitative with a cross-sectional design, involving all 52 employees of Bank Sultra Baubau Branch as respondents through questionnaire distribution. The data were then analyzed using multivariate regression techniques to uncover patterns of relationships among the variables. The results indicate that organizational transformation, employee participation, and interpersonal interaction simultaneously provide a significant boost to employee performance. When analyzed separately, each factor continues to show a meaningful positive effect on productivity improvement. In other words, the more effectively organizational changes, work engagement, and communication quality are implemented, the higher the work achievements attained. These findings emphasize the necessity of a coherent and integrated human resource management strategy to consistently drive organizational performance improvement.